The impact of strategic deviance on analysts' earnings forecasts: evidence from China. Issue 3 (5th August 2019) - He, Xiqiong; Yin, Changping
Abstract : Purpose: The purpose of this paper is to explore the effect of firm's deviant strategy on analysts' earnings forecasts and further examine the effects of firm's information transparency and environmental uncertainty on these relationships from information asymmetry perspective. Design/methodology/approach: The sample includes listed firms on Shanghai and Shenzhen Stock Exchange during the period 2007-2013. Findings: The results indicate that firms' deviant strategies have effects on analysts' earnings forecasts, in particular, firms with extreme strategies have less analysts following, larger forecast error and dispersion compared with firms following industry norms. Moreover, information transparency and environmental uncertainty have effects on the relationship between strategic deviance and analysts' earnings forecasts. Practical implications: The empirical results of this paper provide strong evidence that strategy information is an important source of information for analysts' earnings forecasts, which shows that analysts should pay attention to not only financial information but also the strategic information, especially when the information is related to strategic choice. In addition, it is necessary for investors to focus on strategic information to have a better understanding on financial information of enterprises and make better investment decisions. Originality/value: The findings of this study indicate that corporate strategic deviance has an effect on analysts' earnings forecasting behavior. This study enriches research studies on corporate strategy and external stakeholders and complements related research on analysts' earnings forecasts from strategic perspective and information asymmetry perspective.